2016
DOI: 10.1093/ntr/ntv285
|View full text |Cite
|
Sign up to set email alerts
|

The Language of Cigar Use: Focus Group Findings on Cigar Product Terminology

Abstract: Introduction The consumption of cigar products has increased since 2000. The multiple product types within this category, combined with the varied language with which consumers refer to them, present challenges for accurately assessing the prevalence of cigar product use. Surveillance is also complicated by the fact that these products can be used to smoke marijuana, as “blunts”— cigars in which the tobacco is removed and replaced with marijuana. Few studies exist regarding the language and terminology used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…These users might not consider themselves to be tobacco product users, and thus, might not consider themselves to be at risk for tobacco-related disease or death (6,7). For example, one focus group study with adult cigar smokers found that some users would only use the term "smoker" or "cigar smoker" to describe someone who smoked cigars several times a week or daily (8). This finding underscores the importance of further research on the ascertainment of tobacco product use, as well as efforts to educate the public about the potential harms of all tobacco product use, including risks associated with occasional use.…”
Section: Discussionmentioning
confidence: 99%
“…These users might not consider themselves to be tobacco product users, and thus, might not consider themselves to be at risk for tobacco-related disease or death (6,7). For example, one focus group study with adult cigar smokers found that some users would only use the term "smoker" or "cigar smoker" to describe someone who smoked cigars several times a week or daily (8). This finding underscores the importance of further research on the ascertainment of tobacco product use, as well as efforts to educate the public about the potential harms of all tobacco product use, including risks associated with occasional use.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has found that youth and young adults identify these as unique products used in different situations. 61,62 There may be differences in acquisition and situational use among subtypes of users or by demographic characteristics that cannot be detected owing to CCLC measurement. Despite these limitations, this work allows for examination of CCLC acquisition and situational use within a population, a topic necessary for determining evidence-based interventions and policies for CCLCs.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that whereas use of LCCs as “blunts,” with marijuana replacing some or all of the tobacco inside, is popular with some user subgroups, 35, 36 we did not explore such use in this study. Prior research has implied that respondents may respond differently to usage questions depending on whether the definition provided includes use with marijuana or as “blunts.” 35,37 Reasons for use and perceptions of addiction may vary widely based on the type of substance smoked. 34 …”
Section: Discussionmentioning
confidence: 99%